Drug Design Strategies for the Treatment of Viral Disease. Plant Phenolic Compounds and Their Derivatives - Kowalczyk, Monika; Golonko, Aleksandra; Świsłocka, Renata; Kalinowska, Monika; Parcheta, Monika; Swiergiel, Artur; Lewandowski, Włodzimierz (Frontiers in Pharmacology, 2021)
The coronavirus pandemic (SARS CoV-2) that has existed for over a year, constantly forces scientists to search for drugs against this virus. In silico research and selected experimental data have shown that compounds of natural origin such as phenolic acids and flavonoids have promising antiviral potential. Phenolic compounds inhibit multiplication of viruses at various stages of the viral life cycle, e.g. attachment (disturbance of the interaction between cellular and viral receptors), penetration (inhibition of viral pseudo-particle fusion to the host membrane), replication (inhibition of integrase and 3C-like protease), assembly and maturation (inhibition of microsomal triglyceride transfer protein (MTP) activity hydrolysis) and release (inhibition of secretion of apolipoprotein B (apoB) from infected cells). Phenolic compounds also indirectly influence on the viral life cycle by affecting the host cell’s biochemical processes that viruses use for their own benefit. Phenolic compounds may inhibit the proteasomes and cellular deubiquitinating activity that causes an increase in the ubiquitinated proteins level in host cells. This, in turn, contributes to the lowering the available ubiquitin molecules that viruses could use for their own replication. One of the drug design strategy for the treatment of viral diseases may be an enhancement of the antiviral properties of phenolic compounds by metal complexation. Many studies have shown that the presence of a metal ion in the structure can significantly affect the affinity of the compound to key structural elements of the SARS CoV-2, such as Mpro protease, RNA-dependent RNA polymerase (RdRp) and spike protein. We believe that in the era of coronavirus pandemic, it is necessary to reconsider the search for therapeutics among well-known compounds of plant origin and their metal complexes.